2017
DOI: 10.1037/cdp0000147
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of California mental health professionals in relation to sociodemographic characteristics.

Abstract: Policy and advocacy efforts in health service psychology can help assure more equitable distribution of mental health services. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…California not only has the largest Latino population in the country, encompassing nearly 40% of the state and a large immigrant population (37% of Latinos in California are foreign-born), but is also overwhelmingly home to Mexican-origin Latinos, which represent the largest subgroup in the nation ( U.S. Census Bureau, 2019 ). The social ecology of the state contains a diversity of large urban regions, 21 rural counties, large agriculture and migrant labor sectors, and numerous areas with limited or inequitable health resources, including drug treatment and harm reduction access ( Langabeer et al., 2020 , Rocha, 2017 , Sharma et al., 2017 ). Thus, with Latinos making up a growing proportion of the US, California provides a unique opportunity to understand the nature and extent of opioid overdoses for Latino subgroups living in distinct contexts across the state.…”
Section: Introductionmentioning
confidence: 99%
“…California not only has the largest Latino population in the country, encompassing nearly 40% of the state and a large immigrant population (37% of Latinos in California are foreign-born), but is also overwhelmingly home to Mexican-origin Latinos, which represent the largest subgroup in the nation ( U.S. Census Bureau, 2019 ). The social ecology of the state contains a diversity of large urban regions, 21 rural counties, large agriculture and migrant labor sectors, and numerous areas with limited or inequitable health resources, including drug treatment and harm reduction access ( Langabeer et al., 2020 , Rocha, 2017 , Sharma et al., 2017 ). Thus, with Latinos making up a growing proportion of the US, California provides a unique opportunity to understand the nature and extent of opioid overdoses for Latino subgroups living in distinct contexts across the state.…”
Section: Introductionmentioning
confidence: 99%
“…In general, access to mental health services affects people in poverty the most since the mental health care density tends to be lower in less affluent areas (Ellis et al, 2009 ; Hendryx, 2008 ; Sharma et al, 2017 ). As researchers have pointed out, “we might expect such programs to be located farther away from higher-poverty areas in order to attract fee-paying clients.…”
Section: Introductionmentioning
confidence: 99%
“…Even on the coasts of the United States, distribution of psychologists is uneven. Sharma, Casas, Crawford, and Mills (2017) found that in California, licensed psychologists were clustered in the population centers of the state, and in areas in which residents were older, more educated, wealthier, and more likely White. Given this, it is important that education, employment, and public health stakeholders understand more about the pipeline in psychology as it pertains to individual patterns and choices.…”
mentioning
confidence: 99%